Powering the future: A survey of ambient RF‐based communication systems for next‐gen wireless networks - Shweta Singh; Manish Kumar; Rahul Kumar (IET Wireless Sensor Systems)
Abstract Emerging wireless communication networks, exemplified by the evolution from 5G to subsequent technologies, necessitate extensive connectivity among myriad devices to fuel the ongoing technological progress. However, the magnitude of this network demands an extensive power source, requiring an advanced and sustainable system to be practically deployable. This study introduces a cutting‐edge system utilising ambient RF signals for both wireless information transfer (WIT) and wireless power transfer. The proposed system addresses the energy deficiencies of billions of low‐powered wireless devices within the network. Wireless‐powered communication networks (WPCN) and simultaneous wireless energy and power transfer (SWIPT) technologies, operating on ambient RF signals, provide a solution for the energy requirements of these devices. Harvesting energy from ambient RF signals is pivotal for the signal transmissions of WPCN and SWIPT systems. The research focuses on enhancing the efficiency and feasibility of such systems, emphasising aspects like maximising energy efficiency (EE) and improving outage performance (OP). The paper underscores the ubiquitous connectivity resulting from node mobility and delves into the emerging models of WPCN and SWIPT, along with collaborative technologies integrated with these models. It explores resource allocation (RA), multiple‐input multiple‐output (MIMO) technology in the context of WPCN, and various aspects of relaying operations, including SWIPT‐MIMO and SWIPT receiver architecture. Conclusively, the comprehensive survey affirms that leveraging ambient RF signals for WIT and power transfer can significantly enhance EE, OP, RA, and overall network capabilities. This improvement positions the proposed system as a promising solution for meeting the connectivity demands of future wireless communication technologies.